Risk assessment of new sequencing information for genetically modified soybean BPS‐CV127‐9. (21st September 2018) - ,; Papadopoulou, Nikoletta; Ramon, Matthew
Abstract: The GMO Panel has previously assessed genetically modified (GM) soybean BPS‐CV127‐9. This soybean was found to be as safe and nutritious as its conventional counterpart and commercial soybean varieties with respect to potential effects on human and animal health and the environment in the context of its intended uses. On 16 February 2018, European Commission requested EFSA to analyse new nucleic acid sequencing data and updated bioinformatics data for GM soybean BPS‐CV127‐9 and to indicate whether the previous conclusions of the GMO Panel on safety of GM soybean BPS‐CV127‐9 remain valid. The new sequencing data indicated a two nucleotide difference in the unannotated Arabidopsis genomic DNA sequence downstream of the 3′ untranslated region of the ahasl (also referred to as csr1‐2 ) gene as compared to the sequencing data originally provided. One of these nucleotide differences reported in the new nucleic acid sequencing data from GM soybean event BPS‐CV127‐9 was shown to be already present in the original plant material used for the risk assessment. However, for the other nucleotide difference reported, no evidence could be provided to differentiate between a sequencing error and point‐mutation. With the exception of bioinformatics analyses, the studies performed for the risk assessment of the single event soybean BPS‐CV127‐9 remain valid. The new sequencing data and the bioinformatics analyses performed on the new sequence did not give rise to safety issues. Therefore, EFSA concludes that the original risk assessment of soybean BPS‐CV127‐9 remains valid.